Beamforming design for energy-constrained full-duplex two-way relaying system - Wei WANG; Liyuan AN; Guoan ZHANG; Shibing ZHANG (Tongxin xuebao)
A beamforming design was proposed under simultaneous wireless information and power transfer (SWIPT) protocol.A utility optimization problem was considered aiming to maximize the harvested energy by jointly optimizing the beamforming matrix,the power splitting ratio at the relay and the transmit powers at the sources.Since the formulated joint optimization problem was nonconvex,it was difficult or even intractable to obtain the global optimal solution.To overcome this issue,the objective problem into three subproblems was decoupled which could be solved by the proposed semidefinite relaxation technique and the derived constraints activation solution,respectively.The solution was finally obtained with the proposed convergent iterative algorithm.Simulation results show that the proposed joint optimization scheme achieves the optimal performance.Compared with the traditional half-duplex (HD) algorithm,the proposed algorithm can obtain 2~3 times energy harvesting (EH) efficiency improvement,while the computational complexity increases slightly.